Diet and feeding strategy of smooth butterfly ray Gymnura micrura in northeastern Brazil - Yokota, L. [UNESP]; Goitein, R. [UNESP]; Gianeti, M. D.; Lessa, R. T. P. (Wiley-Blackwell, 2013)
The purpose of the present study was to analyze the diet of the smooth butterfly ray Gymnura micrura using qualitative and quantitative approaches to describe the feeding spectrum as well as ecological aspects related to feeding and niche width. The rays were obtained through monthly sampling as by-catch from bottom trawl fisheries in northeastern Brazil from August 2007 to July 2008. A total of 286 stomachs were sampled, of which 176 contained food items. G.micrura is a predator in the region that feeds intermittently on large whole prey items, followed by a long period of digestion with simply little or no feeding activity. A low diversity of food items was found in the G.micrura diet, with an absolute predominance of teleosts, especially the roughneck grunt Pomadasys corvinaeformis. It is suggested that the species has a narrow feeding niche and a high degree of specialization. This presumed high degree of feeding specialization is discussed and the findings are compared in light of similar studies for closely related species, allowing to propose the family as primarily constituting piscivorous rays.